2018
DOI: 10.1016/j.ajog.2017.12.220
|View full text |Cite
|
Sign up to set email alerts
|

Regular exercisers have stronger pelvic floor muscles than nonregular exercisers at midpregnancy

Abstract: Regular exercisers at midpregnancy have stronger pelvic floor muscles than their sedentary counterparts. However, pelvic floor muscle strength and not regular general exercise was associated with urinary incontinence. There is a need for additional studies in elite athletes and women performing more strenuous exercise regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…While exercising women at 37 weeks' gestation had stronger PFM than non-exercising women, the UI prevalence was not different between groups, after adjusting for PFM training, age, pre-pregnancy body mass index, education and smoking [38]. An adjusted linear regression model showed that PFM strength, rather than being a regular exerciser, was associated with continence.…”
Section: Ui and Pfm Strength In Exercisersmentioning
confidence: 82%
See 2 more Smart Citations
“…While exercising women at 37 weeks' gestation had stronger PFM than non-exercising women, the UI prevalence was not different between groups, after adjusting for PFM training, age, pre-pregnancy body mass index, education and smoking [38]. An adjusted linear regression model showed that PFM strength, rather than being a regular exerciser, was associated with continence.…”
Section: Ui and Pfm Strength In Exercisersmentioning
confidence: 82%
“…In a group of 41 women, PFM strength correlated with aerobic capacity and also with habitual physical activity measured by questionnaire [37]. Controlling for PFM training and other factors, primigravid women performing general exercise at 21 week gestation ≥ times per week had stronger and more enduring PFM than non-exercisers [38].…”
Section: Evidence In Support Of Stronger Pfmmentioning
confidence: 91%
See 1 more Smart Citation
“…As for pregnant athletes, physical exercise, outside professional and high-performance fields, may be beneficial in maintaining pelvic floor fitness. Women who exercise regularly in the mid-gestation weeks of pregnancy were found to have more endurance and muscle strength in the PF and 31.2% presented with UI in contrast with 38.4% of nonathlete pregnant women [ 27 ]. However, engaging in high-performance sports does not prevent the multiple pathologies triggered by childbirth, such as low back pain, UI, or fecal incontinence, but neither does it aggravate those symptoms [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than one method has been adopted to obtain a comprehensive understanding of PFM function [22][23] . However, it is difficult to evaluate PFM function and there is no gold standard for such evaluation [24] . Digital vaginal palpation and sEMG evaluation are two common methods to evaluate the strength of PFM.…”
Section: Discussionmentioning
confidence: 99%